(untitled) - Herman, Gail; 1959-; Ong, Cristina (Grosset & Dunlap, 2002)
Spike the dinosaur finds challenges at Halloween when he tries to decide on a costume and when he helps his brother make a jack-o'-lantern.
1
Keywords: Pumpkin; Dinosaurs; Fiction; Brothers; Fiction; Jack-o-lanterns; Fiction; Fiction; Costume; Fiction; Halloween; Fiction; Early reader